The role of nongovernmental organizations in the health sector of the Philippines - Alfiler, Ma. Concepcion P. (1986)
In response to the pressing needs of the poverty stricken individuals and areas, nongovernmental organizations (NGOs) and private voluntary organizations (PVOs) have launched their own community-based health programs many years before the primary health care approach was formally adopted by the Philippine government in 1979. Some NGOs and PVOs Initially extended medical services to the poor who can hardly afford the prohibitive costs of medical treatment. After working in several communities, a number of NGOs realized that providing doleouts did not solve the persistent problems caused by the lack of medical professionals in the rural areas. Thus began efforts at self-reliance In responding to the health needs of the communities concerned which meant going into community organizing and venturing into health financing schemes. This paved the way for the growing importance of the role of NGOs and PVOs in the health sector.
Keywords: Health services; Health care delivery; Medical care financing; Nongovernmental organizations